Evangelicalism and the emerging church: a congregational study of a Vineyard church - Labanow, Cory E. (Explorations in practical, pastoral and empirical theology, 2009)
Approaching the emerging church -- Becoming familiar with Jacobsfield Vineyard -- Hearing the stories of Jacobsfield Vineyard -- Identifying a central theological question -- Reflections for a wider context -- Appendix : JV demographic survey -- Appendix : semi-structured interview questionnaire